2022
DOI: 10.1186/s40795-022-00580-1
|View full text |Cite
|
Sign up to set email alerts
|

Wealth related inequality in women and children malnutrition in the state of Chhattisgarh and Tamil Nadu

Abstract: Background Child and maternal malnutrition are the most serious health risks in India, accounting for 15% of the country’s total disease burden. Malnutrition in children can manifest as ‘stunting’ (low height in relation to age) or ‘wasting’ (low weight in relation to height) or both and underweight or obesity among women. Other nutritional indicators show that India lags behind, with high levels of anaemia in women of reproductive age. The study aims to analyse the wealth related inequalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(74 reference statements)
2
4
0
Order By: Relevance
“…The richest wealth group accounts for 13.5%–18.1% of the burden of AF. These findings are in line with the previous literature ( Kanjilal et al, 2010 ; Karlsson et al, 2021 ; Khadse & Bansod, 2021 ; Kumar et al, 2015 ; Kumar & Paswan, 2021 ; Mokalla & Mendu, 2020 ; Mukhopadhyay & Chakraborty, 2020 ; Nguyen et al, 2021 ; Pathak & Singh, 2011 ; Shirisha et al, 2022 ; Singh et al, 2020 ; Subramanian et al, 2008 ; Subramanyam et al, 2010 ) documenting the wealth inequality in AF. Third, among children with similar NMRF and MRF, children from poor and poorest backgrounds have a higher prevalence of stunting, severe stunting, underweight, and severely underweight compared to children from the richest backgrounds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The richest wealth group accounts for 13.5%–18.1% of the burden of AF. These findings are in line with the previous literature ( Kanjilal et al, 2010 ; Karlsson et al, 2021 ; Khadse & Bansod, 2021 ; Kumar et al, 2015 ; Kumar & Paswan, 2021 ; Mokalla & Mendu, 2020 ; Mukhopadhyay & Chakraborty, 2020 ; Nguyen et al, 2021 ; Pathak & Singh, 2011 ; Shirisha et al, 2022 ; Singh et al, 2020 ; Subramanian et al, 2008 ; Subramanyam et al, 2010 ) documenting the wealth inequality in AF. Third, among children with similar NMRF and MRF, children from poor and poorest backgrounds have a higher prevalence of stunting, severe stunting, underweight, and severely underweight compared to children from the richest backgrounds.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the country's substantial economic growth at an annual average growth rate of more than six percent during the last two decades, India hasn't made significant progress in reducing anthropometric failure (AF) ( Chatterjee, 2021 ). Equally alarming is the persistent poor-rich gap in AF among children within India ( Porwal et al, 2021 ) as its detrimental effects have long-lasting implications that hinder social progress and equality across multiple generations ( Shirisha et al, 2022 ). However, what contributes to this poor-rich gap in AF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis in southeast Asia indicated a higher prevalence of underweight in rural areas compared to urban areas, and a higher prevalence of overweight in urban areas than in rural areas which co-relates with our study [ 29 , 30 ]. In line with the present study, several studies have highlighted higher age, poor women and women with less education as risk factors for undernutrition and anaemia [ 30 , 38 , 39 ]. Geographically, compared to the northern region of India, eastern, western, and southern zonal regions had higher risk for underweight and anaemia which is contrary to earlier reports where southern states such as Kerala and Tamil Nadu were documented as “positive deviants” in some nutrition-related studies compared to northern states [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, follow-up is essential to do to be able to deal quickly and appropriately with growth and development deviations. If deviations are found, then early intervention is carried out so that the growth and development return to normal or the variations do not get heavier 13 . The child's growth and development system is still slow and inaccurate 14 ; No specific and comprehensive data.…”
Section: Introductionmentioning
confidence: 99%